Retroviral restriction: nature's own solution. Issue 6 (December 2016) - Jones, Christopher E.; McKnight, Áine
Abstract : Purpose of review: The present review will discuss recent advances in the development of anti-HIV therapies inspired by studies of the mechanisms of host restriction factor-mediated resistance to HIV infection. Recent findings: Manipulating the interplay between host cell restriction factors and viral accessory factors that overcome them can potentially be therapeutically useful. Preliminarily successful therapies – some of which are entering clinical trials – either inhibit the ability of virus to evade restriction factor-mediated immunity, or promote intracellular levels of restriction factors. These aims are achieved by multiple means, which are discussed. Summary: Many restriction factors appear to provide potentially useful targets for anti-HIV therapies, so time and interest should be invested in investigating ways to successfully therapeutically manipulate restriction factor-mediated immunity.